Internal consistency and convergent and divergent validity of the Liverpool jetlag questionnaire. (1st February 2020) - Ledger, Susan; Bin, Yu Sun; Nour, Monica; Cistulli, Peter; Bauman, Adrian; Allman-Farinelli, Margaret; Naismith, Sharon L.; Stamatakis, Emmanuel; Caillaud, Corinne; De Chazal, Philip; Simpson, Stephen J.
ABSTRACT: Objective measures of circadian disruption are difficult to capture in a free-living environment hence the importance of validating subjective measures of jetlag. We aimed to assess the internal consistency of the 15-item Liverpool Jetlag Scale and its convergent and divergent validity with indicators of fatigue and anxiety in a large sample of air passengers. Online survey of passengers was conducted after travel on a range of long-haul flights. Jetlag was captured using the Liverpool scale, fatigue was measured using the Vitality subscale of the Short-Form Health Survey (SF-36), and the presence of anxiety or worry before, during, and after flight was self-reported. Inter-item correlations and Cronbach's alpha were calculated to assess the internal consistency of the scale. Exploratory factor analysis was used to examine whether the scale was consistent with one underlying construct of circadian disruption. Correlations between fatigue and anxiety (flying, situational, symptoms) with jetlag were used to assess convergent and divergent validity. Linear regression was used to determine the most important symptoms contributing to subjective jetlag rating. N = 460 passengers (57% female, mean age 50, SD 16 years) were surveyed. Cronbach's alpha indicated high internal reliability (alpha = 0.85). Jetlag was more strongly correlated with fatigue (rho = 0.47) than any type of anxiety (rho = 0.10–0.22). Exploratory factor analysis indicated responses were consistent with four factors: (i) fatigue/daytime impairment, (ii) sleep disturbance, (iii) changes in appetite and (iv) changes in bowel function. Regression analysis indicated that only changes in concentration, sleep time, fatigue, sleep quality and frequency of bowel motions were independent correlates of subjective jetlag (R 2 = 27%). The Liverpool Jetlag Scale is internally consistent and demonstrates the expected relationships with fatigue and anxiety. Patterns of response are not consistent with all items being derived from one underlying factor, i.e. circadian disruption. Further, not all items contributed to the jetlag rating, suggesting the single-item rating may be useful for capturing the subjective experience of jetlag, whilst a total jetlag score is useful for also capturing circadian symptoms considered by passengers to be unrelated to jetlag. Validation of subjective jetlag against objective measures of circadian disruption is required.